2008
DOI: 10.1152/ajprenal.00619.2007
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone improves aortic arginine transport, through inhibition of PKCα, in uremic rats

Abstract: Peroxisome proliferator-activated receptor (PPAR) agonists were shown to inhibit atherosclerosis through augmentation of endothelial nitric oxide synthase (eNOS) activity. In addition, rosiglitazone exerts a beneficial effect in chronic renal failure (CRF). Since l-arginine transport by CAT-1 (the specific arginine transporter for eNOS) is inhibited in uremia, we aimed to explore the effect of rosiglitazone on arginine transport in CRF. Arginine uptake by aortic rings was studied in control animals, rats, 6 wk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 35 publications
3
24
0
Order By: Relevance
“…This suggests that exercise mediates an increase in L-arginine uptake through a posttranslational modification of CAT-1. Previous work by Ingbir et al (25) reported similar results in which treatment of uremic rats with rosiglitazone improved L-arginine uptake in aortic rings without increasing CAT-1 protein expression. Rosiglitazone treatment was associated with a decrease in aortic PKC␣ protein expression and an increase in CAT-1 phosphorylation, suggesting that PKC␣ is an important mediator of CAT-1 transport activity (25).…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…This suggests that exercise mediates an increase in L-arginine uptake through a posttranslational modification of CAT-1. Previous work by Ingbir et al (25) reported similar results in which treatment of uremic rats with rosiglitazone improved L-arginine uptake in aortic rings without increasing CAT-1 protein expression. Rosiglitazone treatment was associated with a decrease in aortic PKC␣ protein expression and an increase in CAT-1 phosphorylation, suggesting that PKC␣ is an important mediator of CAT-1 transport activity (25).…”
Section: Discussionsupporting
confidence: 52%
“…Previous work by Ingbir et al (25) reported similar results in which treatment of uremic rats with rosiglitazone improved L-arginine uptake in aortic rings without increasing CAT-1 protein expression. Rosiglitazone treatment was associated with a decrease in aortic PKC␣ protein expression and an increase in CAT-1 phosphorylation, suggesting that PKC␣ is an important mediator of CAT-1 transport activity (25). In the present study, we observed an increase in PKC␣ expression in the aortas of SED animals whereas levels were returned to similar levels as SHAM animals in both RUN and RUNϩARG treatment groups.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…We hypothesize that delivery of transported arginine to membrane-bound eNOS, selectively by the cationic amino acid transporter-1 (CAT-1) rather than intra- or extra-cellular arginine concentration, is the predominant factor governing eNOS activity. Indeed, we have previously shown in several different animal models characterized by endothelial dysfunction and decreased eNOS activity that CAT-1 activity is attenuated [15,16,17,18]. The predominant mechanism resulting in diminished CAT-1 activity in all these experiments was post-translational modulation of CAT-1 by protein kinase C α (PKCα) [15,17,18].…”
Section: Introductionmentioning
confidence: 99%